Ectomesenchymal Chondromyxoid Tumor: A Neoplasm Characterized by Recurrent RREB1-MKL2 Fusions. (October 2018) - Dickson, Brendan C.; Antonescu, Cristina R.; Argyris, Prokopios P.; Bilodeau, Elizabeth A.; Bullock, Martin J.; Freedman, Paul D.; Gnepp, Douglas R.; Jordan, Richard C.; Koutlas, Ioannis G.; Lee, Cheng-Han; Leong, Iona; Merzianu, Mihai; et al.
Abstract : Ectomesenchymal chondromyxoid tumor is a rare and benign neoplasm with a predilection for the anterior dorsal tongue. Despite morphologic heterogeneity, most cases are characterized by a proliferation of bland spindle cells with a distinctive reticular growth pattern and myxoid stroma. The immunophenotype of these neoplasms is likewise variable; most cases express glial fibrillary acid protein and S100 protein, with inconsistent reports of keratin and myoid marker expression. The molecular pathogenesis is poorly understood; however, a subset of cases has been reported to harbor EWSR1 gene rearrangement. Following identification of an RREB1-MKL2 fusion gene by RNA Sequencing in an index patient, a retrospective review of additional cases of ectomesenchymal chondromyxoid tumors was performed to better characterize the clinical, immunohistochemical, and molecular attributes of this neoplasm. A total of 21 cases were included in this series. A marked predisposition for the dorsal tongue was confirmed. Most cases conformed to prior morphologic descriptions; however, hypercellularity, hyalinized stroma, and necrosis were rare attributes not previously emphasized. The neoplastic cells frequently coexpressed glial fibrillary acid protein, S100 protein, keratin, smooth muscle actin, and/or desmin; a single case was found to contain significant myogenin expression. An RREB1-MKL2 fusion product was identified in 19 tumors (90%), a single tumor (5%) had an EWSR1-CREM fusion product, and the remaining case lacked any known fusion gene by RNA Sequencing. The latter 2 cases subtly differed morphologically from many in the cohort. This series illustrates that recurrent RREB1-MKL2 fusions occur in most, perhaps all, cases of ectomesenchymal chondromyxoid tumor. Abstract : Supplemental Digital Content is available in the text.